Pengaruh Metode Point Counterpoint Terhadap Kemampuan Berpikir Kritis Peserta Didik Mata Pelajaran Akidah Akhlak - Raudlatul Jannah (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
Educators are key instruments of learning, their main task is to educate, teach, guide, evaluate and develop the potential of students. One that needs to be developed in students is critical thinking skills, so appropriate learning methods are needed to improve it. This study aims to determine the effect of the Point Counterpoint learning method on the critical thinking skills of students in class V MI Al-Azhar Aqidah Akhlak subject with a Quasi Experimental Design type quantitative research approach. The test instrument used is a multiple choice test. From the results of descriptive statistical analysis the mean value in the experimental class was initially 65.42 to 70.60 while in the control class it was initially 65.04 to 67.81. The normality test results with the Kolmogorov-Smirnov data obtained were not normally distributed, then data analysis using the non-parametric statistical Wilcoxon test obtained a sig value of 0.000 <0.05. Zcount -4.822 > Ztable 1.96 and Mann Whitney U test sig value of 0.013 <0.05 and Zcount -2.490 > Ztable 1.96. Then Ha is accepted, which means that there is no significant effect of the point counter point learning method on the critical thinking skills.